Configuration of carved components and its layout patterns in Malay timber houses - Kamarudin, Zumahiran; Said, Ismail (Archnet, MIT, United States, 2011)
This paper aims to highlight the carving composition within a specific configuration of pattern formed according to the shape, size and layout of the carved components and its placement in the different forms of traditional houses of Kelantan and Terengganu, Malaysia. Archival research was used as the principal method of data collection, which includes an analytical review of measured drawings of the Kelantan and Terengganu timber houses from the Centre for the Study of Built Environment in the Malay World at the Universiti Teknologi Malaysia. Interviews with two prominent woodcarvers for insightful information on the art and craft of woodcarving were also conducted to augment the principal method. The study found that architectural components of the houses like walls, doors and windows, railings, roofs and gable ends were equipped with carvings in different layout of patterns with distinctive features and visual orders including horizontal, vertical and mixed arrangement. Inasmuch the patterns of layouts were in parallel with the functional aspects of various carved components fabricated as perforated ventilation panels of walls, doors and windows, railing panels, decorative wall panels and panels at gable ends. The patterns were in agreement with the nomenclature of their placements within the house fabric.